Project Management - Mohannad Abu Semri; Mohammad abu-Alia; Omar Bassam Daour; Abed-Allah Sameer Sawalmeh (My University, 2011)
The purpose of the project is to calculate the real quantities referring to Executive scheme for a school building consist of three layers.This project is based on the calculation of real amounts of materials by reading the outline and the plans of a school consisting of three floors,The team was assigned to calculate the quantities of all materials needed to complete the whole construction, annex, of concrete and rebar and formwork, andfinishing work ..... etc, the team has searching for the appropriate production rates of the local environment of Palestine, were calculated by the time schedule of all activities